2015
DOI: 10.1515/aep-2015-0035
|View full text |Cite
|
Sign up to set email alerts
|

Detection of antibiotic resistance genes in wastewater treatment plant – molecular and classical approach

Abstract: Antibiotics are a group of substances potentially harmful to the environment. They can play a role in bacterial resistance transfer among pathogenic and non-pathogenic bacteria. In this experiment three representatives of medically important chemotherapeutics, confi rmed to be present in high concentrations in wastewater treatment plants with HPLC analysis were used: erythromycin, sulfamethoxazole and trimethoprim. Erythromycin concentration in activated sludge was not higher than 20 ng L , respectively in win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 29 publications
(30 reference statements)
2
8
0
Order By: Relevance
“…In the same year, Grape et al (2003) detected this gene in E. coli recovered (Perreten and Boerlin, 2003). According to the studies of Wu et al (2010) and Ziembińska-Buczyńska et al (2015), sul3 gene is the least prevalent one in E. coli strains recovered from human and animal resources, this data is in parallel with the present results. Although, sul3 gene was rarely detected in the studied isolates (4% only), this small percentage should be considered as it may be a warning sign revealing that its existence can be widespread in the locality.…”
Section: Discussionsupporting
confidence: 88%
“…In the same year, Grape et al (2003) detected this gene in E. coli recovered (Perreten and Boerlin, 2003). According to the studies of Wu et al (2010) and Ziembińska-Buczyńska et al (2015), sul3 gene is the least prevalent one in E. coli strains recovered from human and animal resources, this data is in parallel with the present results. Although, sul3 gene was rarely detected in the studied isolates (4% only), this small percentage should be considered as it may be a warning sign revealing that its existence can be widespread in the locality.…”
Section: Discussionsupporting
confidence: 88%
“…In a study by Ziembińska-Buczyńska et al, [17] total bacterial counts in activated sludge fluctuated between 12x10 9 CFU/mL in samples collected in summer and 42x10 9 CFU/mL in winter, and they increased steadily between winter and spring months. The cited authors also reported higher counts of bacteria resistant to erythromycin and sulfamethoxazole/trimethoprim in samples from winter.…”
Section: Resultsmentioning
confidence: 94%
“…The presence in the aquatic ecosystems of intestinal bacteria, originating from WWTPs, may have a negative impact on public health because of these bacteria can be characterized by multi-drug resistance and they frequently possess ARGs or virulence genes [11,28]. Additionally, these ARB can transmit resistance to native bacteria from the environment, including both pathogenic or non-pathogenic bacteria, mediated by mobile genetic elements, such as plasmids (conjugation), bacteriophages (transduction), or free DNA from the environment (transformation) [11,17]. The obtained results indicate the presence of ARB also in river water before and after the inflow of WWTPs, which may pose a threat to human health and animals using water resources.…”
Section: Resultsmentioning
confidence: 99%
“…The results are consistent with other studies conducted globally. For example, in a study by Ziembińska-Buczyńska et al (2015) on communal WWTP in Zabrze (Poland), dfr and sul1 genes were detected in most of the sample tested from influent, effluent and downstream. In another study, sul1 together with int1 were also detected in samples from WWTP and the downstream environments (Sayah et al, 2005).…”
Section: Diversity and Dynamics Of Antibiotic Resistance Genes In Difmentioning
confidence: 99%